Toward a reference material for line profile analysis. (22nd December 2014) - Troian, Andrea; Rebuffi, Luca; Leoni, Matteo; Scardi, Paolo
Abstract : A powder obtained by ball milling a commercial FeMo alloy has been identified and investigated as possible reference material for powder diffraction line profile analysis. Ball milling yields micrometer-scale agglomerate particles made of rounded nanocrystalline domains with extensive lattice defects, so as to produce both size and strain contributions to the line profiles. The capability of a modern whole-powder pattern modeling to accurately quantify those aspects and the stability of the powder over a decade are shown and discussed.